Penerapan Model Project-Based Learning Untuk Meningkatkan Hasil Belajar Materi Keragaman Budaya di Sekolah Dasar Indonesia - Fauziah, Anisa; Imaniah, Riksa Suci; Sukmanasa, Elly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
The purpose of this research is to improve learning outcomes by implementing a project-based learning model. The research subjects were off class IV with 35 students at SD Negeri Polisi 2 Bogor. The results of the research show that the success of applying the project-based learning model can improve student learning outcomes. This is evidenced by the learning outcomes of cycle I of students who were declared complete as many as 16 students and as many as 20 students who did not complete. The learning completeness of classical students reached 45.7% with an average value of 69.5. While the acquisition of learning outcomes in cycle II there were 31 students or 88.6% who achieved completeness with an average score of 80.5 and 4 students or 11.4% were declared incomplete. The completeness of students learning outcomes classically in cycle II has increased compared to cycle I only reaching 45.7% increasing to 88.6% in cycle II. Thus it can be concluded that this research has a positive and significant impact on the "Implementation of the Project Based Learning Model to Improve Learning Outcomes of Cultural Diversity Materials in Indonesia". The results of this study are expected to provide new knowledge about the influence of innovative, creative learning models and can improve student learning outcomes.